Hardness Analysis of Stone Breaker Chisel Made of Medium Carbon Steel as a Result of Hardening Using Water Cooling Media - Novendra, Alan; Refdinal, Refdinal; Le, Sai Kham (Universitas Negeri Padang, 2020)
Stone chisels produced by blacksmiths which are made using leaf spring steel are often too brittle or fragile so that when they are used, they often occur in the form of cracks and breaks. This study aims to determine the appropriate hardness level for stone chisels. The process is carried out by comparing the hardness level of stone chisels that have been used but still in good condition and those that have been damaged. Broken stone chisels have a high adequate hardness compared to good stone chisels so that damaged stone chisels can be reconditioned to get the right rock chisel hardness. Heat treatment is given to damaged stone chisels to improve the hardness level by normalizing the process to restore the initial mechanical properties of the steel and increasing the hardness of the chisel by heating the steel and then quenching it using water cooling media. Based on the experimental process carried out that the hardness level of a good stone chisel is between 228 HB to 320 HB by heating the duan spring steel to a temperature of 780ºC with a hold time of 10 minutes then cooling it quickly using water and stone chisels can break when it is used because it has a very high hardness.